Properties of Malaysian Coconut-Breed (MATAG, MAWA, and Pandan) Yogurts: A Preliminary Analysis of Chemical, Microbiological, and Sensorial Characteristics (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
The conversion of coconut milk (CM) into yogurt may enhance its nutritional qualities and acceptance as a sustainable alternative to dairy. Three types of CM (Pandan, MATAG, and MAWA) were analyzed for protein and fat content using the Kjeldahl and Gerber method, respectively. Commercial plant-based starter culture was utilized to produce yogurts, with Pandan CM showing the highest lactic acid bacteria count (>109 CFU/mL). Consequently, sensory analysis with 50 untrained panelists revealed no significant differences between Pandan CM yogurt and dairy yogurt in terms of texture, flavor, sourness, creaminess, and overall acceptability. The study suggests that coconut yogurt is a microbiologically and commercially viable option, suitable for consumers preferring plant-based products and sustainability practices.
Keywords: Plant-based milk; Coconut milk; Proximate; Probiotic; Hedonic